Analysis of nutritional status of children at state elementary School Kampung Rawa 02 Central Jakarta - Jenny Anna Siauta; Gani Putri Aryanto; Rukmaini Rukmaini; Yenny Aulya (Institute of Computer Science (IOCS), 2026)
Nutritional status is a crucial indicator influencing children's growth and development, health, and academic achievement. Nutritional issues in elementary school-aged children remain a public health issue, with both undernutrition and overnutrition and obesity contributing to growth disorders and the risk of future disease. To analyze the nutritional status of children at SDN Kampung Rawa 02, Central Jakarta, and the factors influencing it. This study used a quantitative cross-sectional design. The sample consisted of 148 students in grades 4–6. Data were analyzed using the chi-square test. Data were collected through questionnaires and BMI/Ag measurement using a microtoise and scales. Univariate and bivariate analyses were performed. The proportion of children with nutritional status showed undernutrition (7.4%), overnutrition (47.3%), and obesity (15.5%). The majority of respondents reported poor eating and drinking habits (56.1%), insufficient physical activity (66.2%), an unsupportive environment (55.4%), and insufficient family involvement (60.1%). Bivariate analysis showed a significant relationship between knowledge level (p=0.02), eating and drinking behavior (p=0.006), physical activity (p=0.01), environment (p=0.03), and family role (p=0.01) and children's nutritional status. The nutritional status of children at SDN Kampung Rawa 02, Central Jakarta, indicates nutritional problems, including undernutrition, overnutrition, and obesity. Factors such as knowledge level, eating and drinking behavior, physical activity, environment, and family role play a role in influencing children's nutritional status. Nutrition education and school and family support are needed to maintain children's nutritional status.